Nurses' knowledge about post-cardiopulmonary arrest patient care: an integrative review (Research, Society and Development, 2023)
Objective: To analyze nurses’ learning about patient care Post-Cardiopulmonary Arrest (post-CPA). Method: Integrative, exploratory review that sought studies written between the years 2012 to 2022 that were related to the proficiency of nurses in post-cardiac arrest care. The subsequent databases existed used to filter these studies: Google Scholar, Latin American and Caribbean Literature in Health Sciences (LILACS), PUBMED, International Medical and Biomedical Literature (MEDLINE), Specialized Bibliography in the Area of Nursing (BDENF), Scientific Electronic Library Online (SCIELO). For the search, the following descriptors available on the Descriptors in Health Sciences (DeCS) website were used: Nursing knowledge, Cardiopulmonary arrest and nursing care, using the Boolean operator “AND” Inclusion criterion: delimitation within the period 2012-2022, being in the Portuguese language and having addressed the theme. Exclusion criterion: repetition of studies, out of the thematic axis, and out of the above-mentioned language. Results: Distribution of the main care mentioned were: Hemodynamic monitoring, verification of vital signs and monitoring of therapeutic hypothermia, followed by blood gas collection, pervious airways, transfer to intensive care unit. Conclusion: There is a deficiency of theoretical and practical knowledge of some nursing professionals about post-CPA care. Continuous education must be prioritized since nursing professionals themselves have the technical and scientific competence to develop these skills and provide optimal care to post-CPA patients.